Using Creativity Supportive Classrooms For Improving Secondary Stage Students EFL Speaking Skills and Reducing Their Anxiety - Gohar, Rehab Hamadtoh Abualghait (جامعة القاهرة - كلية الدراسات العليا للتربية, 2018)
This study aimed at assessing the effect of using creativity-supportive classrooms on improving 1st year secondary stage students’ EFL speaking skills and reducing their speaking anxiety. Pronunciation, fluency, accuracy and vocabulary were the major speaking skills targeted in the current study. The proposed creativity-supportive classroom addressed the creativity aspects of originality, fluency, flexibility and elaboration through employing creative teacher practices, teaching for creativity and assessment for creativity in a constructive manner that helped the students to construct their knowledge and enhance their skills. Multiple creativity-supportive speaking techniques (e.g. talking circles, simulation, interactive games, storytelling, etc.) were used and reflected in different scenarios for engaging students in different speaking tasks. In addition, authentic formative assessment tasks, self-assessment, and oral informative feedback were employed. Participants of the study were (50) first year secondary stage students. The quasi-experimental design was adopted in which the participants were equally assigned into two groups: a control group (studied through the regular speaking classes) and an experimental group (studied through the creativity-supportive classroom). Instruments used in the study were a speaking skills test with an analytic rubric for assessing and scoring the oral speaking performance of the students and an anxiety scale for measuring students’ anxiety level. Results revealed that the experimental group students outperformed their counterparts of the control group in the target EFL speaking skills. Besides, the speaking anxiety post-level of the experimental group was reduced compared to their prelevel and to the control group’s post anxiety level as well. Accordingly, the creativity-supportive classroom proved its effectiveness in improving 1st year secondary stage students’ speaking skills and reducing their speaking anxiety.
Keywords: التعليم الثانوي -- تدريس اللغة الإنجليزية -- المهارات اللغوية -- الوسائل التعليمية